(untitled) (Sains Humanika, 2013)
This article analyses gender wage differentials in the most modern sector in Malaysia that is information and communication technology (ICT). This sector is chosen based on its characteristics, which are modern, sophisticated and has more complete information, where employers’ behaviour on hiring workers and paying wages is perceived as more objective and rational. Analysis involves two stages, first, estimating the wage models separately for males and females based on Mincer (1974) schooling model to identify the wage determinants. Second, decompose the gender wage differentials based on Blinder (1973) method. The analysis uses the data collected in 2007/2008, comprises of 347 professional and executive workers in the ICT sector in Selangor and Federal Territory of Kuala Lumpur. Results from the estimation show that education, training, study location and ethnicity are significant in determining males and female’s wages. However, the result from the wage decomposition shows that gender wage differentials is highly influenced by employers’ bad perception or discrimination against women, whereby the contribution of this portion is close to 80 per cent. This reflects that the sophisticated with perfect information sector such as the ICT sector does not guarantee a good conduct of the employers.